Verifying the suitability of uncoupled numerical methods for solving vehicle-bridge interaction problems - González, Arturo; Covián, Enrique; Casero, Miguel (Structure and infrastructure engineering, 2023)
The response of a structure subjected to a moving load can be obtained using coupled or uncoupled methods. The uncoupled method is often preferred since modal superposition is applicable, which implies computational efficiency and ease of implementation. However, the uncoupled method ignores the changes in the dynamic features of the combined structural system due to the time-varying location of the load. This paper analyses the extent to which the accuracy of the uncoupled method is affected by these changes. First, a parametric study is conducted on two discretized beam models traversed by a sprung mass at a constant speed. The error associated with the uncoupled method is calculated using the coupled solution as a reference. The influence of the load to structure mass and frequency ratios and the speed of the vehicle on the error is quantified. Heavier loads travelling at higher speeds are found to increase the inaccuracy of the uncoupled method. Then, the analysis is extended to a half-car travelling on a rough profile. Although errors from the uncoupled simulation remain low for the range of parameters under investigation, they may not be acceptable in some applications, i.e., the training of an algorithm for early damage detection.